Friction factor for turbulent flow in rough pipes from Heisenberg's closure hypothesis - Calzetta, Esteban Adolfo (2009)
We show that the main results of the analysis of the friction factor for turbulent pipe flow reported by Gioia and Chakraborty [Phys. Rev. Lett. 96, 044502 (2006)] can be recovered by assuming the Heisenberg closure hypothesis for the turbulent spectrum. This highlights the structural features of the turbulent spectrum underlying the analysis of Gioia and Chakraborty. © 2009 The American Physical Society.